Leader humility and employees’ creative performance: the role of intrinsic motivation and work engagement - Liu, Haiou; Jameel Ahmed, Syed; Anjum, Muhammad Adeel; Mina, Azalim (Frontiers in Psychology, 2024)
Drawing on the job demand-resource (JD-R) model and self-determination theory (SDT), this study examines the relationship between humble leadership and employees’ creative performance, taking into account the sequential mediating role of intrinsic motivation and work engagement. The sequential mediation model was tested using two-wave questionnaire data collected from employees and their supervisors (n = 350) in the telecommunication sector of Pakistan. Data were processed and examined using SPSS and AMOS. The results revealed significant positive relationships among all variables. Further, it was found that intrinsic motivation and work engagement sequentially but partially mediated the positive relationship between humble leadership and creative performance. The theoretical and practical implications are discussed at the end.